Is manganese (II) pentaazamacrocyclic superoxide dismutase mimic beneficial for human sperm mitochondria function and motility? - Otasevic, Vesna; Korac, Aleksandra; Vucetic, Milica; MacAnovic, Biljana; Garalejic, Eliana; Ivanovic-Burmazovic, Ivana; Filipovic, Milos; Buzadzic, Biljana; Stancic, Ana; Jankovic, Aleksandra; Velickovic, Ksenija; Golic, Igor; et al. (Antioxidants & Redox Signaling, 2013)
Mitochondria play an important role in sperm cell maturation and function. Here, we examined whether (and how) changes in sperm redox milieu affect the functional status of sperm mitochondria, that is, sperm functionality. Compared with the control, incubation in Tyrode's medium for 3 h, under noncapacitating conditions, decreased sperm motility, the amount of nitric oxide (.NO), the number of MitoTracker Green FM (MT-G) positive mitochondria, and the expression of complexes I and IV of the mitochondrial respiratory chain. In turn, superoxide dismutase (SOD) mimic (M40403) treatment restored/increased these parameters, as well as the expression of endothelial nitric oxide synthase, manganese SOD, and catalase. These data lead to the hypothesis that M40403 improves mitochondrial functional state and motility of spermatozoa, as well as.NO might be involved in the observed effects of the mimic. © 2013, Mary Ann Liebert, Inc.